Modelo de evaluación basado en la calidad total para valorar la calidad educativa en la educación básica - Mas Sandoval, Héctor Grober (2014)
The present research, descriptive, was intended to demonstrate that the proposal and implementation of the evaluation model based on total quality allows to assess the educational quality of the public educational institution Nº 81002 “Javier Heraud” district of Trujillo, in the year 2012. The population consisted of 620 members of the educational community (teachers, parents and students). And the sample about 324 members. The instruments were provided questionnaires, which were applied to members of the sample. As a result of the investigation was concluded that the purpose and the application of the evaluation model based on total quality education possible to assess the quality of public school Nº 81002 “Javier Heraud” district of Trujillo, obtaining as a result: the educational quality is in the low level with some factors in the average level and none in the high level, remaining reified the hypothesis of study.